Where do physicians start and end?. Issue 12 (December 2016) - H Ellaway, Rachel; Topps, David; Topps, Maureen
Abstract: Medical education is primarily about training physicians and maintaining their capabilities over time. Given that physicians are the primary focus of the field, there is a need for a clear idea of what physicians are or could be. This paper seeks to explore this issue by posing the simple question: ?Where do physicians start and end?' In doing so, the authors explore a series of different conceptual frames, including those of a physician's physical dimensions, their cellular boundaries, personal intentions and beliefs, professional identity, regulation, entrustability, professional performance, extended cognition, and disability. This existential look at the concept of a physician demonstrates the plurality of medical education scholarship and the implications of the many intersecting points of view in the field. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.